Analyzing Technological Innovation Diffusion: An Evolutionary Game Approach from a Dual Supply-Demand Perspective - Zhang, Zhiwen; Xu, Xiaodi; Li, Yi (Advances in Social Sciences Research Journal, 2026)
This study investigates the diffusion of technological innovation within a market-driven framework by employing evolutionary game analysis. We develop a model from a dual supply-demand perspective, integrating enterprise production and consumer purchasing behavior. The model incorporates market variables such as revenue, costs, and consumer characteristics, utilizing MATLAB software for simulation to assess the impact of these factors on the strategic decisions of both enterprises and consumers. The findings reveal that the perceived value of innovative products and consumer acceptance facilitate the diffusion of technological innovation, whereas the perceived value and perceived loss associated with traditional products hinder this diffusion. Furthermore, the propensity of enterprises to adopt technological innovations is strongly linked to consumer demand for innovative products, with enterprises showing a greater inclination to embrace new technologies in response to heightened innovation demand.